2002
DOI: 10.1016/s0022-5347(05)64636-8
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Cystopathy Correlates With a Long-Term Decrease in Nerve Growth Factor Levels in The Bladder and Lumbosacral Dorsal Root Ganglia

Abstract: PURPOSE It has been proposed that a deficiency in the axonal transport of nerve growth factor (NGF) may have an important role in inducing diabetic neuropathy, which contributes to diabetic cystopathy. Therefore, in streptozotocin (Sigma Chemical Co., St. Louis, Missouri) induced diabetic rats we investigated the relationship of bladder function with NGF levels in the bladder and lumbosacral dorsal root ganglia, which contain afferent neurons innervating the bladder. MATERIALS AND METHODS At 6 and 12 weeks aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
101
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 124 publications
(112 citation statements)
references
References 29 publications
9
101
0
1
Order By: Relevance
“…It has been recently reported in STZinduced diabetic rats that decreased NGF levels in the bladder and lumbosacral dorsal root ganglia are associated with bladder dysfunction, suggesting the feasibility of NGF gene therapy for the treatment of diabetic cystopathy (36).…”
Section: Pathophysiologymentioning
confidence: 99%
“…It has been recently reported in STZinduced diabetic rats that decreased NGF levels in the bladder and lumbosacral dorsal root ganglia are associated with bladder dysfunction, suggesting the feasibility of NGF gene therapy for the treatment of diabetic cystopathy (36).…”
Section: Pathophysiologymentioning
confidence: 99%
“…Aδ-fiber and some C-fiber afferents are mechanosensitive and respond to bladder filling by providing information about bladder wall tension and volume 3,4 . Neuro-pathological conditions can selectively impair the functioning of specific subpopulation of nerve fibers while sparing the others 1,5 . Therefore, diagnosing dysfunction in specific subpopulations of bladder afferent fibers in the neurogenic bladder, may be helpful in guiding therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there are several publications suggesting that diabetes-associated bladder pathology is mainly a result of alterations in neuronal components, including deficiency of acetylcholinesterase (5-7), impaired ATPase activity (8,9), and diminished neurotrophic factor (10,11). Recently Sasaki et al (12) and Goins et al (13) showed the relation between bladder dysfunction and lower nerve growth factor levels and the feasibility of nerve growth factor gene therapy for treating diabetes mellitus (DM) 1 cystopathy.…”
mentioning
confidence: 99%